The persistence of cyanobacterial (Microcystis spp.) blooms throughout winter in Lake Taihu, China. (17th December 2015) - Ma, Jianrong; Qin, Boqiang; Paerl, Hans W.; Brookes, Justin D.; Hall, Nathan S.; Shi, Kun; Zhou, Yongqiang; Guo, Jinsong; Li, Zhe; Xu, Hai; Wu, Tingfeng; Long, Shengxing
Abstract: Temperature is generally considered as a key factor controlling algal bloom formation. Previous studies have indicated that the bloom‐forming cyanobacteria Microcystis spp. overwinters near the sediment surface and does not actively grow below 15°C. However, satellite images and field collections from Lake Taihu, China have shown that Microcystis spp. blooms persisted when water temperatures were below 10°C during winter, although their magnitudes were smaller than during periods of higher temperature. Winter Microcystis cells maintained low activity and were able to grow again when exposed to elevated temperatures (≥12.5°C). Hence, cyanobacterial blooms may appear year‐round in eutrophic lakes. Temperature increases coupled with nutrient enrichment promoted the growth of cyanobacteria, while low temperature decreased the loss rate of Microcystis, allowing winter blooms to persist. High concentrations of overwintering vegetative cells may provide a large inoculum for blooms during warmer seasons. Controlling winter blooms may reduce their magnitude during the warmer seasons.